O papel do profissional de Relações Públicas como gestor da comunicação para a educação do público interno - Calonego, Renata [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
This study is the result of theoretical and practices reflections that sought to understand the role of the professional of Public Relations as educator and manager of the communication process in the digital age. For the theoretical foundation of the theme, started from an overview to the subject, with a historical context of capitalism and its attendant changes in the global scenario. Were discussed, later, the model of dialogic communication interaction, which is the building space of dialogue between organization and internal public. Comes a new vision for the role of public relations in educational activities for communication, due to the capacity of this professional to diagnose, predict, assess and implement projects, which may enable the rediscovery of the subject in its social, cultural and human dimensions. From this perspective, the professional of PR needs to promote the humanization of man and visualize a communication to action, which involves the transmission of information exchange, reflection, reciprocity and dialogue. The overall objective of this study was to analyze the educational role of internal communication, considering the performance of the professional of public relations as a communicator and educator of the communication process in the digital age. Thus, the specific objectives of this research, supported in a methodology qualitative, quantitative and a case study, consisted of a more critical analysis to compare the level of development of internal communication for education in two organizational frameworks -Brazilian and English- of Nestlé company, under the light of the organizational culture and interactional dialogic model and, in the verification of which competences are essential to the communicator play the role of educator and which competences should be generated in the internal public to occur formation, considering which features a virtual environment need to have to provide it, since it is a space that..

Este estudo é resultado de reflexões teóricas e práticas que buscaram compreender a atuação do profissional de Relações Públicas como gestor e educador do processo comunicacional na era digital. Para o embasamento teórico acerca do tema, partiu de uma visão geral, com a contextualização histórica do capitalismo e suas consequentes transformações no cenário globalizado. Aborda-se, posteriormente, o modelo de interação comunicacional dialógica, que é o espaço de construção da interlocução entre organização e público interno. Surge uma nova concepção para a atuação das Relações Públicas em ações educativas para a comunicação, por ser um profissional capaz de diagnosticar, prognosticar, assessorar e implementar projetos, podendo viabilizar a redescoberta do sujeito em suas dimensões social, cultural e humana. Sob essa perspectiva, o profissional de Relações Públicas precisa promover a humanização do homem e visualizar uma comunicação para ação, onde a transmissão de informação implica a troca, reflexão, reciprocidade e diálogo. O objetivo geral desse estudo consistiu em a nalisar o papel educativo da comunicação interna, considerando a atuação do profissional de Relações Públicas como comunicador e educador do processo comunicacional, na era digital. Diante disso, os objetivos específicos dessa pesquisa, amparados em uma metodologia qualitativa, quantitativa e de estudo de caso, consistiram em uma análise mais crítica ao comparar o nível de desenvolvimento da comunicação interna voltada para a educação em dois âmbitos organizacionais -brasileiro e inglês- da empresa Nestlé, sob à luz da cultura organizacional e do modelo interacional dialógico e, na verificação de quais competências são essenciais para o comunicador desempenhar o papel de educador e quais competências devem ser geradas no público interno para que ocorra sua formação, considerando quais funcionalidades
Keywords: Educação; Comunicação - Aspectos econômicos; Relações publicas; Comunicação nas organizações; Competencia comunicativa; Education